Heat, clay and aromatic units: a mechanism for making macromolecules in the early solar system - Watson,JS; Sephton,MA (Astrobiology, 2015)
The major organic component in carbonaceous chondrites is ahighly aromatic macromolecular material. Aromatic organic matter andphyllosilicates are co-located in these meteorites and it is possible that thephysical association represents a synthetic chemical relationship. To explore thepotential reactions that could take place to produce the aromatic macromolecularmaterial we heated various simple aromatic units in the presence ofmontmorillonite with different exchanged cations. The majority of cationexchanged montmorillonites tested, sodium-, aluminium-, iron-, nickel- andcobalt-rich montmorillonites, do not produce polymerisation products. By contrastFe3+ cation exchanged montmorillonite readily facilitates addition reactionsbetween aromatic hydrocarbons. A feasible mechanism for the process isoxidative coupling which involves a corresponding reduction of the Fe3+ cation to its Fe2+ counterpart. A similar reduction process for the other metal cations does not take place highlighting the importance of iron. This simple process is a feasible mechanism for the addition to the aromatic macromolecules such as thosefound in carbonaceous chondrites. The search for a relationship between Fe3+-richphyllosilicates and aromatic organic structures (particularly dimers, trimers and more polymerised forms) in carbonaceous chondrites would represent an effective test for constraining the role of clay catalysis in the early solar system.